Effects of Applied Psychosocial Treatment Program in Substance Abuse Patients, Kong Krailat District, Sukhothai Province - ลือชูวงศ์ มงคล (Journal of Health Science of Thailand, 2024)
This study employed a prospective observational design to examine the efficacy of applied psychosocial treatment program with substance use disorder in Kong Krailat Hospital, Sukhothai province. The samples consisted of 134 substances users attending outpatient clinic at the hospital during January to July 2023. The participants underwent a 4-month applied psychosocial treatment program. Data were collected through interviews on substance use history, the national drug abuse report form and emotional quotient assessment; and the data were analyzed by using descriptive analysis and Chi-square test. The results revealed that the majority of samples were male, aged 31-40 years, single, highest education level of high school, working as general laborers, and monthly incomes below 3,000 baht. Nearly two-thirds of participants started using substance before the age of 20 (63.4%), with peer influence (44.0%) and curiosity (28.4%) being the main reasons. Results from the intervention treatment program showed that 93.7% of participants completed the 4-month program, with 76.1% were able to abstain from substance use for 3 months. Moreover, the participants showed improved emotional intelligence levels with most falling within the normal to high range. Age, education level, monthly income, and reasons for the initial substance use were positively correlated with the ability to abstain from substance use for 3 months. The applied psychosocial treatment program combined with emotional intelligence enhancement was found to be effective in treating substance abuse patients in a small, resource-limited community hospital.